2020
DOI: 10.1002/jmri.27209
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic Analysis of Native T1 Mapping Images Discriminates Between MYH7 and MYBPC3‐Related Hypertrophic Cardiomyopathy

Abstract: Background: The phenotype via conventional cardiac MRI analysis of MYH7 (β-myosin heavy chain)-and MYBPC3 (β-myosin-binding protein C)-associated hypertrophic cardiomyopathy (HCM) groups is similar. Few studies exist on the genotypic-phenotypic association as assessed by machine learning in HCM patients. Purpose: To explore the phenotypic differences based on radiomics analysis of T 1 mapping images between MYH7 and MYBPC3-associated HCM subgroups. Study Type: Prospective observational study. Subjects: In all,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Pathogenic or likely pathogenic variants in sarcomere protein encoding genes can be identified in 40-60% of adolescents and adults affected by HCM. MYBPC3 (encoding cardiac myosin binding protein-C, cMyBPC) and MYH7 (encoding β cardiac myosin heavy chain) account for the majority of cases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic or likely pathogenic variants in sarcomere protein encoding genes can be identified in 40-60% of adolescents and adults affected by HCM. MYBPC3 (encoding cardiac myosin binding protein-C, cMyBPC) and MYH7 (encoding β cardiac myosin heavy chain) account for the majority of cases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies failed in the majority to demonstrate phenotypic differences between MYBPC3 and MYH7 mutation carriers. Some imaging studies were suggestive of a more severe phenotype in individuals carrying a pathogenic genetic variant in MYH7 mutations compared to MYBPC3, although differences were often marginal and non-significant [3,8,12]. Other studies found no significant differences with regard to parameters of left ventricular (LV) function and structure, and myocardial scar formation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The myocardium was initially manually delineated with the endocardial and epicardial contours and the radiomic features were subsequently extracted from the myocardium ROI. A total of 157 features was extracted from the T1 mapping for each participant and the process of image filtering and feature extraction was performed with MATLAB 2014 (MathWorks, Natick, MA, USA), which is consistent with previous study 24 . PyRadiomics of Python (https://github.com/Radiomics/pyradiomics) was used to extract features from the annotated regions, including Gray Level Cooccurence Matrix (GLCM), Gray Level Run Length Matrix (GLRLM), Gray Level Size Zone Matrix (GLSZM), Gray Level Dependence Matrix (GLDM) and Neighborhood Gray Tone Difference Matrix (NGTDM), as well as filtered features (Laplacian of Gaussian, Wavelet, Square, Square Root, Logarithm Exponential, Gradient, and Local Binary Pattern).…”
Section: Methodsmentioning
confidence: 99%
“…Our research center used 0.15 mmol/kg to detect T1 mapping for many years. Some researches have been reported (25)(26)(27). Figure 1 shows the contrast-enhanced T1 maps of two PA patients and two EH patients.…”
Section: Cardiovascular Magnetic Resonance Protocolmentioning
confidence: 99%